Prevenção de práticas de manipulação de resultados e melhoria da qualidade do relato financeiro na validação das políticas contabilísticas, alterações de estimativas e erros - Silva, Lurdes (2023)
Purpose: The objective of this study is to assess the perception of audit professionals on the importance of adopting Accounting and Financial Reporting Standard (NRCF) 4 - Accounting Policies, Changes in Accounting Estimates and Errors and International Accounting Standard (IAS) 8 - Accounting Policies, Changes in Accounting Estimates and Errors, essentially with regard to the prevention of profit manipulation practices and the improvement of the quality of financial reporting. Methodology: A qualitative methodology was adopted by conducting structured interviews with four audit professionals. Results: The interviewees consider that the auditor plays an important role in the application of value judgments and validation of estimates, stating that their work is a deterrent to the practice of profit manipulation. They also consider that the auditor's ethics, professional skepticism, and degree of independence contribute to an improvement in the quality of financial reporting and a decrease in profit manipulation practices. Research limitations: The lack of literature on the application of accounting policies, changes in estimates, and errors; the difficulty in gaining acceptance to conduct the interviews; and the limitations associated with conducting interviews were the main limitations encountered. Originality: This study is innovative in that it gathers the opinion of auditors and chartered accountants on a very relevant matter in the accounting field, given that standards increasingly call for the application of value judgments in defining accounting policies and estimates, as well as in changing them and detecting errors.